Kroppar, dislokationer och politiska praktiker på YouTube - Johansson, Anna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
This article explores the benefits of political discourse theory in the analysis of self harm video blogs. It is argued that a reworked concept of ‘dislocation’ (e.g. Laclau 1985, 1990; Glynos & Howarth 2007) can shed light on the chaotic experiences prior to the act of self harm, and it is further claimed that this act, as well as the practice of video blogging, can be seen as responses to the dislocatory experience. On the explicit level, the videos often challenge the stigma of self harm, and especially the stigma of self injury scars. However, drawing on Glynos and Howarth’s four dimensions of social practices (social, political, ethical, ideological), the article demonstrates how many of the video blogs simultaneously contest and conform to this stigmatisation. It is suggested that a categorisation according to the four dimensions can be used as a first step in the analysis ofsocial practices.